[Use of health care services by patients with co-occurring severe mental illness and substance use disorders] - KEDOTE, MARIUS; Brousselle, Astrid; Champagne, Francois (My University, 2008)
Background: To better respond to the health care needs of people with co-occurring mental illness and substance use disorders, it is vital to understand their itinerary through the health care system. Aim: To describe the characteristics of service utilization among patients with co- occurring disorders in a large urban area. Method: We used a sample (n ¼ 5467) constituted from administrative and clinical databases. Those identiﬁed as having substance use disorders and psychoses were followed over 12 months with respect to their utilization of medical services. A descriptive analysis of the data and a two-step cluster analysis were undertaken. Results: Our analyses revealed a relatively high utilization of emergency services, outpatient clinics, private practices and hospitalization among patients with co- occurring disorders of severe mental illness and substance use. The two-step cluster analysis produced four heterogeneous groups in terms of service utilization. Conclusions: This study demonstrates the need to develop strategies for organizing health care and services that are adapted to various sites of service utilization and to diverse proﬁles of patients with co-occurring mental illness and substance use disorders.
Keywords: co-morbidity; co-occurring; mental health; substance use disorders; service utilization